Use of bee-attractants in increasing crop productivity in Niger (Guizotia abyssinica. L) - Sivaram, Venkataramegowda; Jayaramappa, Koragandahalli Venkateshappa; Menon, Anita; Ceballos, Ruben Michael (Brazilian Archives of Biology and Technology, 2013)
The use of bee attractants, Bee-Q and Fruit Boost((TM)) in the pollination of niger was evaluated. Bee visitations to niger flowers were observed for two weeks and an estimation of seed yield was determined. Different concentrations of Bee-Q and Fruit boost((TM)) were evaluated to understand honeybee visitation patterns on the target crop and pollination efficiency. Results indicate that applications of Bee-Q at 12.5 g/l and Fruit boost at 0.75 ml/l on niger plots significantly increased the number of bee foragers over control plots. In addition, plots sprayed with these bee attractants significantly enhanced the seed set, seed weight, and germination of niger. This study suggests that pheromone-based bee attractants applied to niger can increase the marginal percentage of bee visitation, seed yield, and percent germination.